Les marqueurs discursifs du français: un regard croisé sur une catégorie controversée - Vladimirska, Elena; Gridina, Jelena; Turlā-Pastare, Daina (Kalbotyra, 2021)
In this paper, we discuss the question of discourse markers (DM) – a category conceived differently by theoretical and applied linguistic approaches. Unlike in applied approaches, in which DMs are considered desemantized/grammaticalized lexical units devoid of their own semantics and therefore of status in the language, we consider DMs to constitute a full-fledged category of language, having its own semantics and distribution, both of which play a crucial role in the construction of discourse (Paillard 2011, 2012; Franckel 2008, 2019). This hypothesis has been developed in theoretical linguistics and has seen little evidence from a perspective of the acquisition and didactics of foreign languages. Based on cross-analysis of linguistic theories (Benveniste 1974; Ducrot 1980; Hopper & Traugott 1993; Culioli 1990,1999; Franckel & Paillard 2008) and on distributional analysis of data of the spoken corpora, we show that the absence of specific linguistic status for DMs has repercussions at the didactic and acquisition levels: DMs are generally approached in an ad hoc manner, all functions combined, which leads on the one hand to gaps in the acquisition of French and, on the other hand, to the ambiguity of criteria for evaluation. Therefore, at the level of applied linguistics, we suggest the integration of DMs in the learning path as a full category, an integration that must be carried out on several axes – semantic, syntax and prosodic – and be based on an authentic oral corpora of the spoken language. At the theoretical level, we use transversal analysis in order to give yet another argument in favor of a semantical-enunciative approach to discursive markers.